2017
DOI: 10.1186/s12889-017-4778-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fidelity in individual level behaviour change interventions promoting physical activity among adults: a systematic review

Abstract: BackgroundBehaviour change interventions that promote physical activity have major implications for health and well-being. Measuring intervention fidelity is crucial in determining the extent to which an intervention is delivered as intended, therefore increasing scientific confidence about effectiveness. However, we lack a clear overview of how well intervention fidelity is typically assessed in physical activity trials.MethodsA systematic literature search was conducted to identify peer - reviewed physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 64 publications
3
101
0
Order By: Relevance
“…Firstly, the study made use of a comprehensive treatment fidelity framework (Bellg et al ., ), to conduct a methodologically rigorous assessment of the implementation of the delivery of a walking intervention by health care professionals to their own patients. As the staff delivering the intervention in this study were not members of the research team and were delivering the intervention as part of their routine work, the findings of the research are likely to be more representative of routine clinical practice, than many findings reported in the research literature (Lambert et al ., ; Walton et al ., ). However, it is possible that the intensity of contact between the research team and providers, as a result of monitoring and interview participation, may have contributed to the level of adherence identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the study made use of a comprehensive treatment fidelity framework (Bellg et al ., ), to conduct a methodologically rigorous assessment of the implementation of the delivery of a walking intervention by health care professionals to their own patients. As the staff delivering the intervention in this study were not members of the research team and were delivering the intervention as part of their routine work, the findings of the research are likely to be more representative of routine clinical practice, than many findings reported in the research literature (Lambert et al ., ; Walton et al ., ). However, it is possible that the intensity of contact between the research team and providers, as a result of monitoring and interview participation, may have contributed to the level of adherence identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…When fidelity is investigated in studies of PA interventions, significant heterogeneity in methodological rigour and quality has been identified. A 2017 systematic review of treatment fidelity in PA behaviour change trials found only one study ensured providers were trained to a well‐defined a priori performance criterion, few studies used objective data collection methods to assess delivery; and the quality, expertise, and reliability of fidelity raters were rarely examined (Lambert et al ., ). Likewise, assessment of treatment receipt, that is, participant's understanding of the intervention content, was rarely investigated.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Physiotherapy behaviour change interventions (O'Shea, Mccormick, Bradley, & O'Neill, 2016) . Physical activity behaviour change (Lambert et al, 2017) 2. Limited focus beyond assessing fidelity of delivery .…”
Section: Issues With Intervention Fidelitywhat Is Not Being Done Andmentioning
confidence: 99%
“…The strengths of this study were the mixed data collection and integrating the qualitative component in a real-life setting to understand contextual factors during the intervention that might affect the outcome (Craig et al, 2013). A particular strength of our evaluation was addressing intervention fidelity based on a framework recommended by others (Lambert et al, 2017;Rixon et al, 2016).…”
Section: Methodological Considerationsmentioning
confidence: 99%